Ownership characteristics, related party transactions and firm performance : analysis of listed firms in Nigeria - Olanrewaju, Aminu Sikiru (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Related party transactions (RPTs) have been a delicate and important phenomenon in accounting debates. Its effects on firm performance have been studied extensively in the developed Western market. The study of related party transactions in developing and emerging markets have been minimal due to weak corporate governance structures. Most of the empirical evidence in this regard relied heavily on the agency theory of “principal-agent” relationship based on the proposition that the ownership structure of firms is diffused. Recent studies have on the contrary, provided empirical studies pointing to the concentrated nature of ownership structures around the world tweaking the agency theory to a “principal-principal” relationship. The results, therefore, remain inconclusive. Compelling among the causes of the discrepancies include structures of ownership and differences in legal and cultural environments of reporting entities. As a result, emerging accounting literature on corporate governance is challenging the status quo arguing for the inclusion of country specific variables in the governance codes at the height of the International Financial Reporting Standards (IFRS) convergence agenda. As a response to these critical observations, this study focused on Nigeria, an emerging economy with a concentrated ownership structure, in an attempt to analyze how related party transactions impact the relationship between ownership characteristics and performance of firms listed on the Nigerian Stock Exchange (NSE). Standard panel regression method was used to analyze the available data for the chosen study period (2010-2013). The results of the study showed that only the ethnic composition of the board of directors was statistically significant and confirmed the apriori expectation of the study. This goes to show that country-specific corporate governance variables should be accorded more cognizance in accounting studies. In general, the results showed that, for the non-financial listed firms on the stock market of Nigeria, the moderating effect of RPTs was not significant statistically across the corporate governance variables in relation to firm performance except for the ethnic composition of the board of directors. Finally, the study also showed that despite the evolving nature of corporate governance codes in Nigeria, the results of the non-financial sub-sector of the listed firms portray some level of compliance with existing codes and operate within the ambits of global best practices.